(untitled) (Journal of Atomic and Molecular Sciences, 2011)
By using Lie dynamical algebra representation theory, we have solved the master equation for the nondegenerate parametric amplifier model in a thermal reservoir. Applying a series of transformations, we show that the master equation has multiple commuted SU(1,1) Lie algebra structures. The explicit solution to the master equation has been obtained.